PATHWAYS TO PERSEVERANCE: MYCORRHIZATION AS A STRATEGY FOR SUSTAINABLE FARMING IN HIGH-TEMPERATURE CONDITIONS - Thompson, Emily Roberts; Howard, Michael James (Ayden Journal of Agriculture and Allied Studies, 2024)
The escalating impacts of climate change on crop growth and yields, particularly the challenges posed by heat and drought stress, are driving the demand for climate-resilient agricultural technologies and practices. To counteract these adversities and sustain agricultural productivity, a pivotal role is being played by advancements in science and technology. Nature itself has proven proficient in facilitating plant development even in adverse conditions. Within the intricate web of soil biology and ecosystem interactions, the symbiotic relationship between plant roots and arbuscular mycorrhizal fungi (AMF) emerges as a paramount factor in agriculture. AMF represents a vital group of microorganisms that significantly contribute to the microbial biomass in cultivated soils. Remarkably, around 80% of plant species engage in symbiotic associations with these fungi, underscoring their profound importance in enhancing soil quality and crop performance. Notably, various crops such as beans, soybeans, corn, sunflowers, and wheat exhibit symbiosis with approximately 40 species of arbuscular mycorrhizal fungi. This study delves into the crucial interplay between climateinduced challenges, agricultural sustainability, and the role of AMF symbiosis in mitigating adverse effects. By shedding light on these intricate dynamics, it aims to elucidate the significance of AMF in shaping resilient agricultural systems in the face of a changing climate.